TUMPENG ROBYONG SEBAGAI MANIFESTASI KEARIFAN LOKAL DALAM ADAT DAN BUDAYA DESA BEJILOR - Farafishah, Aisah; Suryadi, Yadi (Penerbit Lafadz Jaya, 2026)
The Tumpeng Robyong tradition is a manifestation of local wisdom preserved by the people of Beji Lor Village as a traditional ritual and expression of socio-cultural life. This tradition not only conveys gratitude for sustenance and safety but also philosophical values, cultural symbols, and social functions that strengthen relationships among residents. This research uses a qualitative approach with a descriptive phenomenological method to explore the meaning and social function of the Tumpeng Robyong tradition from the perspective of its key participants. Data were collected through in-depth interviews with traditional leaders, community leaders, and residents involved in the ritual, supported by participant observation and visual documentation. The findings show that Tumpeng Robyong is a symbol of harmony between humans, nature, and God, as well as a medium for transmitting mutual cooperation, gratitude, solidarity, and cultural identity. This tradition plays a crucial role in maintaining social cohesion and the continuity of local wisdom amidst the challenges of modernization.